قضية الاختلاف في تعلق الجار بعامليـن متفقيـن ذكرًا وحذفًا في القرآن الكريم ........................................................ Difference of Opinion in Relating Prepositional Phrase to Express or Omitted Element in the Quran - كوثر, سلمى (الدراسات الإسلامية, 2018)
Among the most important phenomena of speech is the element related to prepositional phrase which can be a verb or a word similar to it. During the study of the Holy Quran, sometimes we see that there exists difference in the element related to the prepositional phrase and this difference affects the meaning. Therefore, the correct meaning depends on the correct correlation whereas false/inaccurate correlation causes the invalidity of the meaning. Proper identification of this relation determines the correct meaning and eliminates confusion and inaccuracy. This paper aims to highlight the Issue of the attachment of prepositional phrase with the help of two factors agreeing in citation and elision in the Holy Quran. These elements related to the prepositional phrase may be expressed or omitted or there may be allowed two manifestations in them. But it is inevitable for the scholars of Islam to determine the nearest manifestation or farthest one or unacceptable manifestation or acceptable one. For this reason, this study has a major impact on the way of understanding the meanings and connotations of the verses more correctly and any negligence in this regard can be a barrier in reaching to the intended meaning.